Use of the Ages and Stages Questionnaire and Bayley Scales of Infant Development-II in Neurodevelopmental Follow-up of Extremely Low Birth Weight Infants - Woodward, Barbara J (2011)
OBJECTIVES: For infants born extremely low birth weight (ELBW), we examined the 1) correlation between results on the Ages and Stages Questionnaire (ASQ), and the Bayley Scales of Infant Development II (BSID-II) at 18-22 months corrected age; 2) degree to which earlier ASQ assessments predict later BSID-II results; 3) impact of ASQ use on follow-up study return rates. STUDY DESIGN: ASQ data were collected at 4, 8, 12, and 18-22 months corrected age. The BSID-II was completed at 18-22 months corrected age. ASQ and BSID-II 18 – 22 month sensitivity and specificity were examined. Ability of earlier ASQs to predict later BSID-II scores was examined through linear regression analyses. RESULTS: ASQ sensitivity and specificity at 18-22 months were 73% and 65%, respectively. Moderate correlation existed between earlier ASQ and later BSID-II results. CONCLUSIONS: For ELBW infant assessment, the ASQ cannot substitute for the BSID-II, but appears to improve tracking success.